Effectiveness of Institutional Monetary Instruments at the Disposal of the Polish Central Bank (NBP). Experiences of the NBP’s Two Years of Struggle Against Inflation - Misiński, Wojciech (Skuteczność instytucjonalnych instrumentów monetarnych będących w dyspozycji Narodowego Banku Polskiego (NBP). Doświadczenia dwóch lat walki NBP z inflacją, 2024)
The aim of the article is to attempt to answer three research questions: Was it inevitable that inflation would reach such a high (peak and cumulative) level in Poland? Can the fall in the level of inflation in Poland to the level of the European Union average be considered a real and sustainable success of NBP actions? In the struggle with inflation, did the NBP use all the institutional monetary instruments at its disposal? Methodology: The following methodological assumptions were adopted in the process of presentation, analysis and assessment of institutional monetary instruments. Firstly, as a methodological research requirement, I adopted the recommendation (method of analysis) of Kenneth J. Arrow, according to which analysis of the flow of money provides more information than any other analysis. Secondly, I assessed only the effectiveness of monetary policy instruments in accordance with the methodological assumption, according to which the veracity of statements (the applied monetary instruments) only makes sense in the context of the adopted assumptions (the causes of inflation), whose a priori falsehood determines the falsehood of theories or models (the effectiveness of combatting inflation). Results: The article conducts an analytical and synthetic assessment of the effectiveness of institutional monetary instruments used by the NBP. Implications and recommendations: The analysis provides the basis for presenting recommended changes to the strategy for combatting inflation in the future. Originality/Value: Author’s critical analysis of the effectiveness of the NBP’s use of monetary instruments in the fight against inflation.
Ekonomia XXI Wieku = Economics of the 21st Century, 2024, Nr 27, s. 41-55
Keywords: inflation; new institutional economics; monetary instruments; Narodowy Bank Polski; inflacja; nowa ekonomia instytucjonalna; instrumenty monetarne